The Impact of Capital Structure on Profitability of Mining Companies - Rayhan Daffa Haekal; Hendy Tannady (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to determine how the financial structure of publicly traded mining companies on the Indonesia Stock Exchange (IDX) affects their profitability. The debt-to-equity ratio (DER), which represents the financial structure in this study, is an independent variable. Profitability is a dependent variable that is assessed using the Return on Equity (ROE) ratio. Secondary data from the financial reports of mining companies listed on the IDX from 2020 to 2022 was used in this study. The purposive sampling method was used to choose the sample. Over the course of three years, a total of 63 data points from 21 mining companies listed on the IDX were gathered to satisfy the requirements. Multiple linear regression analyses were used in this study to look at how the variables related to one another. The results of the regression analysis show that both aspects of the financial structure significantly affect both aspects of profitability at the same time. The Return on Equity (ROE) dimension is significantly impacted by solely the debt-to-equity ratio (DER) dimension, though.